ASSESSMENT OF MEDICAL STUDENTS’ METACOGNITIVE AWARENESS OF READING STRATEGIES AND ITS RELATION WITH ACADEMIC PERFORMANCE: A CROSS SECTIONAL STUDY AT AZIZ FATIMA MEDICAL AND DENTAL COLLEGE, FAISALABAD - Subhan Ullah; Sami ullah; Khalid Parvez; Ghulam Abbas Sheikh (Journal of University Medical & Dental College, 2020)
ABSTRACT BACKGROUND & OBJECTIVE: Students reading strategies strongly influence their academic performance. Our study aimed to determine medical students’ metacognitive awareness during reading strategies and its relation with their academic scores. METHODOLOGY: Study was done among third year MBBS students of Aziz Fatima Medical College Faisalabad. Students previous years academic achievement information was collected and they also filled questionnaire on metacognition regulation by the Metacognitive Awareness Reading Strategies Inventory. Convenient sampling was used for this study. The data were analyzed in SPSS 20. In our study the independent variable was metacognitive score while previous professional examination marks were taken as the dependent variable.Standard deviation and mean were used for the descriptive data. For categorical data, percentage and frequencies were used. RESULTS: Different reading strategies employed by medical students in relation to metacognition were our main focus in the study. Metacognition was taken as score measured by a 30 item MARSI scale and their academic performance measured in terms of total marks obtained in the last professional examination held by the University. Total 101 out of 110 students from 3rd year MBBS class were enrolled in the study and the response rate was 92%. Forty one (41) respondents were females and sixty (60) respondents were male the mean± SD age of students was 21.05±0.74. CONCLUSION: All dimensions of metacognition are positive and strongly correlated with each other’s. Higher the score in one dimension will cause positive change in other dimension score and vice versa.